Analysis of resource bottleneck in 4G network - Yuezhen WANG; Ke YIN; Jiansheng LIANG; Yu CHEN (Dianxin kexue)
The technical capability of LTE network was analyzed,which included cell throughput,channel capacity of PDCCH ,PHICH and PUCCH,random access capacity,paging capacity and so on.Then,based on the technical ability,the consumption and occupancy of network resources such as PRB,PDCCH CCE,PUCCH,PRACH,paging,RRC connection were analyzed.Finally,the bottleneck resources which restrict the LTE network to provide more customer service were deduced,and the bottleneck index proposal which focuses on the construction and operation optimization was put forward.